ANTROPOCENE: la "salute" del villaggio globale e il "Cigno Nero" - Alessandro Capitanini (AboutScience Srl, 2022)
Over the past three centuries, the effects of humans on the global environment have increased. It seems appropriate to assign the term "Anthropocene" to the current geological epoch, which is in many ways dominated by humans. The Anthropocene can be said to have begun in the latter part of the 18th century, when analyses of air trapped in polar ice showed the beginning of the rise in global concentrations of carbon dioxide and methane. This date also coincides with the design of the steam engine by James Watt in 1784. In particular, the 21st century witnessed an unforeseen but predictable resurgence of infectious diseases, not least the COVID-19 pandemic, which had a devastating impact on lives and livelihoods worldwide. The 2003 severe acute respiratory syndrome coronavirus outbreak, the 2009 swine flu pandemic, the 2012 Middle East respiratory syndrome coronavirus outbreak, and the 2013-2016 Ebola virus outbreak in West Africa all caused significant morbidity and mortality as they spread through the global village across borders to infect people in multiple countries. In the last 70 years, the speed at which human habits have changed through technological, demographic and climatic changes is unprecedented: airline flights have doubled since 2000, more people live in urban than rural areas since 2007, climate change poses a growing threat to society, and humans have stopped following the high road shown by nature with proper nutrition and regular exercise. In this review, we consider the extent to which these recent global changes have increased the risk of infectious disease outbreaks, even though improved sanitation and access to health care have led to significant progress worldwide.